Translation and evaluation of the Infant Characteristics Questionnaire in a sample of Swedish patients with craniosynostosis - Johanna Kling; Lars Kölby; Marizela Kljajić (Journal of Plastic Surgery and Hand Surgery)
Background: Research on the psychological development of infants with craniosynostosis would benefit from further properly validated tailored measures. Aim: Our study aimed to translate and evaluate the Infant Characteristics Questionnaire (ICQ; Bates et al., 1979) for use with parents of infants with craniosynostosis in Sweden. Methods: Participants included parents of 83 infants (67.5% boys) with isolated craniosynostosis (sagittal: n = 51, metopic: n = 32), and an average age of 184.7 days (SD = 67.1). Parents completed the ICQ and interviews were conducted with 22 of the families. The interviews were analyzed using conventional qualitative content analysis. Results: Reliability in terms of internal consistencies were sufficient for the overall scale (α = .85), the Fussy/Difficult (α = .80) and Unadaptable (α = .76) subscales, close to acceptable for the Unpredictable subscale (α = .66), and low for the Sociable subscale (α = .45). Parents found the ICQ relevant for capturing important aspects of their infants’ temperament, and the instructions and questions easy to understand. However, many parents noted that the question regarding their child’s first reaction to solid food was not applicable and some suggested adding more questions about sleeping difficulties. Conclusion: Overall, the ICQ seems to be acceptable to parents of children with craniosynostosis in Sweden – a prerequisite for continued use and development. Future studies should investigate additional psychometric properties, including factorial validity, to further establish its usefulness in Swedish populations, both with and without craniosynostosis.